Enabling Allogeneic T Cell-Based Therapies: Scalable Stirred-Tank Bioreactor Mediated Manufacturing - Gatla, Himavanth; Uth, Nicholas; Levinson, Yonatan; Navaei, Ali; Sargent, Alex; Ramaswamy, Senthil; Friedrich Ben-Nun, Inbar (Frontiers in Medical Technology, 2022)
Allogeneic T cells are key immune therapeutic cells to fight cancer and other clinical indications. High T cell dose per patient and increasing patient numbers result in a clinical demand for large number of allogeneic T cells. This necessitates a manufacturing platform that can be scaled-up, while retaining cell quality. Here we present a closed and scalable platform for T cell manufacturing to meet clinical demand. Upstream manufacturing steps of T cell activation and expansion are done in-vessel, in a stirred-tank bioreactor. T cell selection, which is necessary for CAR-T based therapy, is done in the bioreactor itself, thus maintaining optimal culture conditions through the selection step. Platform’s attributes of automation and performing the steps of T cell activation, expansion and selection in-vessel, greatly contribute to enhancing process control, cell quality, and to reduction of manual labor and contamination risk. In addition, the viability of integrating a closed, automated, downstream process of cell concentration, is demonstrated. The presented T cell manufacturing platform has scale up capabilities, while preserving key factors of cell quality and process control.